2013
DOI: 10.1371/journal.pone.0060923
|View full text |Cite
|
Sign up to set email alerts
|

Squeezing the Muscle: Compression Clothing and Muscle Metabolism during Recovery from High Intensity Exercise

Abstract: The purpose of this experiment was to investigate skeletal muscle blood flow and glucose uptake in m. biceps (BF) and m. quadriceps femoris (QF) 1) during recovery from high intensity cycle exercise, and 2) while wearing a compression short applying ∼37 mmHg to the thigh muscles. Blood flow and glucose uptake were measured in the compressed and non-compressed leg of 6 healthy men by using positron emission tomography. At baseline blood flow in QF (P = 0.79) and BF (P = 0.90) did not differ between the compress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 46 publications
5
69
4
Order By: Relevance
“…Previous work on this topic found that external compression on a limb leads to a decrease (40 to 84 mm Hg compression),41 no change (≈37 mm Hg compression),42 or increase (13 to 23 mm Hg compression)43 in resting limb blood flow. The conflicting results may relate to differences in techniques, protocols, populations, types of garment, and the range and duration of compression levels.…”
Section: Discussionmentioning
confidence: 97%
“…Previous work on this topic found that external compression on a limb leads to a decrease (40 to 84 mm Hg compression),41 no change (≈37 mm Hg compression),42 or increase (13 to 23 mm Hg compression)43 in resting limb blood flow. The conflicting results may relate to differences in techniques, protocols, populations, types of garment, and the range and duration of compression levels.…”
Section: Discussionmentioning
confidence: 97%
“…Recent meta-analysis suggested that compression values should be taken into account when assessing the meaningfulness and practical relevance of the use of compression clothing in a given situation (5). Some studies suggest that inappropriate compression (too high / tight-fitted garment or too low / loose-fitted garment) could explain negative or no effects (5,22,23). For example, Sperlich et al (2013) demonstrated that, during recovery from high intensity exercise, too high compression (i.e.…”
Section: Objectivesmentioning
confidence: 99%
“…Some studies suggest that inappropriate compression (too high / tight-fitted garment or too low / loose-fitted garment) could explain negative or no effects (5,22,23). For example, Sperlich et al (2013) demonstrated that, during recovery from high intensity exercise, too high compression (i.e. 37 mmHg on the thigh) reduces blood flow both in the deep and superficial regions of muscle tissue (22).…”
Section: Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last decade, compression garments have been proposed as playing a positive role in improving the strength, endurance, and recovery of athletes and patients [1,2]. External compression garments comprise a series of elastic fabric designed to follow the body mold.…”
Section: Introductionmentioning
confidence: 99%